Single Case Research Methodology: Applications in Special Education and Behavioral Sciences, 3rd edition - Jennifer R., Ledford (Routledge, 2020)
Single Case Research Methodology, 3rd Edition presents a thorough, technically sound, user-friendly, and comprehensive discussion of single case research methodology. This book can serve as a detailed and complex reference tool for students, researchers, and practitioners who intend to conduct single case research design studies; interpret findings of single case design studies; or write proposals, manuscripts, or reviews of single case methodology research. The authors present a variety of single case research studies with a wide range of participants, including preschoolers, K-12 students, university students, and adults in a variety of childcare, school, clinical, and community settings, making the book relevant across multiple disciplines in social, educational, and behavioral science including special and general education; school, child, clinical, and neuropsychology; speech, occupational, recreation, and physical therapy; and social work.